Research hotspots and trends in the field of quality of life of oral cancer patients: A visual analysis based on CiteSpace (基于CiteSpace口腔癌患者生活质量研究热点的可视化分析) - YANG Ting (杨婷); CHEN Siyi (陈思忆); ZHENG Xiaodan (郑晓丹); YANG Yi (杨怡) (中西医结合护理)
Objective To explore the research hotspots and trends in the field of quality of life of oral cancer patients, so as to provide a guiding basis for quality of life studies on oral cancer patients in China. Methods Using the literature related to the quality of life of oral cancer patients published in Web of Science from 2000 to 2022 as the data source. The CiteSpace software was used for visual analysis. Results A total of 860 relevant articles were included after removing the duplicates by Citespace, and the number of annual publications basically showed an upward trend. The main body of the researches was concentrated in universities and research institutes in the United States and the United Kingdom, and the institutions and countries have formed a certain scale of cooperative groups. Research hotspots are the factors influencing the quality of life of oral cancer patients, assessment tools for quality of life, interventions and management of influencing factors. Conclusion It is recommended that researchers learn from the advanced theories and models of foreign countries to further develop a quality of life assessment scale more suitable for oral cancer patients in China. In the future, the main focus should be on personalized treatment plans, rehabilitation training methods and management, supportive care needs, and body imagery changes so as to better improve the quality of life of oral cancer patients. (目的 使用文献计量法探讨国际口腔癌患者生活质量研究的热点及趋势, 为我国口腔癌患者生活质量研究提供指导依据。方法 以2000年—2022年Web of Science收录的口腔癌患者生活质量相关文献为数据来源, 运用CiteSpace软件进行可视化分析。结果 经CiteSpace去重后共纳入860篇相关文献, 年度发文量基本呈上升趋势; 研究主体集中在美国和英国的高校及研究所, 各机构和国家形成了一定规模的合作团体; 研究热点为口腔癌患者生活质量的影响因素、生活质量的评估工具、影响因素的干预和管理。结论 建议研究者学习借鉴国外先进理论及模式, 进一步研制更适合我国口腔癌患者的生活质量评估量表。未来应重点关注个性化治疗方案、康复训练方法及管理、支持性照护需求、身体意象改变, 以更好地提高口腔癌患者生活质量。)